2022
DOI: 10.3389/fnins.2022.876142
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Behavioral Detection Thresholds per Electrode via Synchronous, Spatially-Dependent Intracortical Microstimulation

Abstract: Intracortical microstimulation (ICMS) has shown promise in restoring quality of life to patients suffering from paralysis, specifically when used in the primary somatosensory cortex (S1). However, these benefits can be hampered by long-term degradation of electrode performance due to the brain’s foreign body response. Advances in microfabrication techniques have allowed for the development of neuroprostheses with subcellular electrodes, which are characterized by greater versatility and a less detrimental immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…A potential limitation of our results is that all of the electrodes in our study were subject to intracortical microstimulation (ICMS) experiments ( Urdaneta et al, 2019 ; Kunigk et al, 2022 ; Urdaneta et al, 2022 ); it is unclear how this ICMS may have affected recording performance. Despite the lack of unstimulated electrodes as a control group, all microstimulation charges were distributed across all channels.…”
Section: Discussionmentioning
confidence: 99%
“…A potential limitation of our results is that all of the electrodes in our study were subject to intracortical microstimulation (ICMS) experiments ( Urdaneta et al, 2019 ; Kunigk et al, 2022 ; Urdaneta et al, 2022 ); it is unclear how this ICMS may have affected recording performance. Despite the lack of unstimulated electrodes as a control group, all microstimulation charges were distributed across all channels.…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that the sensation features, e.g., sensory perception intensity, spatial discrimination, etc., can be finely tuned by adjusting the stimulation parameters. 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 However, different results were observed: some studies showed a linear positive relationship between stimulation amplitude and magnitude of sensation up to the tested maximal stimulation intensity (16 nC per phase [ph]), 4 , 5 whereas others demonstrated a plateau effect above 12 nC/ph. 4 Schmidt et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although the distribution of neural activation from stimulation is not well understood, it is often assumed that artificial electrical stimulation evokes neural activity spherically from the point of stimulation which lead to the theory of current steering [44][45][46][47]. However, we have shown that the influences of stimulation are different when electrodes are positioned perpendicular to the cortical layers compared to parallel.…”
Section: Differences Between Multilayer and Single-layer Current Stee...mentioning
confidence: 74%
“…Multilayer dual-electrode stimulation for prosthetics would cause the entire column to activate which could make the propagation of the artificial stimulation through the visual hierarchy more likely as more feedforward circuits become active. It has been previously shown that the perelectrode detection thresholds with dual-electrode stimulation decrease regardless of the stimulation layer in rat somatosensory cortex [47]. Given the lack of change in the neural activity curves and peak locations of our dual-electrode data in comparison to the single-electrode data, less charge can be input at two single electrodes while achieving the same level of neural activity in the column.…”
Section: Implications For Cortical Prosthesesmentioning
confidence: 87%